Acute rheumatic fever in adults: Case report together with an analysis of 25 patients with acute rheumatic fever - Nuntana Kasitanon (2018)
We reported the oldest acute rheumatic fever (ARF) patient with initial attack at the age of 90 years and experience with ARF in adults in 20 years of observation. The case files of all ARF patients treated by rheumatology unit, Chiang Mai University, were reviewed. Demographic data and clinical profile were recorded and compared between patients with initial attack and patients with recurrent attack. A total of 25 patients with ARF were included. There was no different incidence of arthritis and carditis between two groups. Initial attack patients have higher incidence of prolonged PR-interval (67 vs. 12%, P = 0.049) and longer duration of admission to diagnosis (5 vs. 2 days, P = 0.05). Thirty percent presented initial attack after 30 years of age. ARF is more common in adults than previously recognized. Therefore, clinicians should be aware of this condition and include it in their differential diagnosis of the febrile patients with arthritis. © 2008 Springer-Verlag.